Green synthesis of neem (Azadirachta indica) functionalized zinc oxide with enhanced antimicrobial properties - Anupam Halder; Gokul Raj Mohan; Saravanan Matheshwaran; Shikhar Krishn Jha (Next Materials)
This study presents an ecofriendly and cost-effective method for synthesizing functionalized zinc oxide (ZnO) nanoparticles using Azadirachta indica (neem) leaf extract. Adding leaf extracts during the synthesis of ZnO led to significant structural and morphological variations, as leaf extract functions as a capping agent and influences the nucleation and growth of ZnO nanoparticles. The micrographs from TEM suggest that the leaf extract addition has significantly reduced the particle size on ZnO. FT-IR and UV-Vis spectroscopy confirmed the presence of functional groups from the leaf extract, which altered the electronic structure and band gap energy. The neem-ZnO nanoparticles showed enhanced antibacterial activity when compared with its reported counterparts, at just 50 µg/ml against the gram-positive bacterium Bacillus subtilis and ∼400 µg/ml against Staphylococcus aureus. Further, the material displayed a distinct antibiofilm activity against the pellicle biofilm formation of Bacillus subtilis, expanding its utility in materials in biomedical engineering and medicinal applications. The tested materials were more effective against gram-positive bacteria than gram-negative bacteria.